Analog circuit design Volume 3: The design note collection - Dobkin, Bob; Hamburger, John (Newnes, 2015)
Design Note Collection, the third book in the Analog Circuit Design series, is a comprehensive volume of applied circuit design solutions, providing elegant and practical design techniques. Design Notes in this volume are focused circuit explanations, easily applied in your own designs. This book includes an extensive power management section, covering switching regulator design, linear regulator design, microprocessor power design, battery management, powering LED lighting, automotive and industrial power design. Other sections span a range of analog design topics, including data conversion,
Includes index. - Online resource; title from title page (Safari, viewed February 5, 2015)
Keywords: Analog integrated circuits -- Design and construction; TECHNOLOGY & ENGINEERING; Mechanical; Circuits intégrés